Status Anak di Luar Pernikahan Menurut Hukum Islam - Sarah Qosim (ADALAH, 2022)
Legitimate children are children born from legal marriages in accordance with the terms and pillars. Meanwhile, adultery children are children born outside a legal marriage. The status of children out of wedlock according to Islamic law has been regulated in the Qur'an and Al-hadith. The problems that then arise include the impact of the status of children outside of marriage. In this article the author reviews briefly and concisely.